Effects of Co-worker and Supervisor Support on Nurses' Energy and Motivation through Role Ambiguity and Psychological Flexibility. (2019) - Blanco-Donoso, Luis Manuel; Moreno-Jiménez, Bernardo; Pereira, Gladis; Garrosa, Eva
Abstract: One of the job resources most strongly associated with nurses' well-being and motivation is social support. However, the psychosocial mechanisms that would explain this relationship have not been sufficiently researched. Thus, the main aim of this study was analyze whether this relationship could be mediated by two variables: role ambiguity and psychological flexibility. A total of 196 nurses from various Spanish hospitals and primary health care centers participated in this cross-sectional study. A multiple mediation analysis was run using the "PROCESS" macro script in SPSS 23.0. The results showed that co-worker support was related to higher levels of vigor and vitality through role ambiguity (Estimate = .158, 95% CI [.050, .298], and Estimate = .212, 95% CI [.076, .390], respectively). The same applied to supervisor support, (Estimate = .197, 95% CI [.059, .378], and Estimate = .212, 95% CI [.076, .390], respectively). Co-worker support was also related to higher levels of vigor and vitality through psychological flexibility, (Estimate = .132, 95% CI [.048, .271], and Estimate = .216, 95% CI [.086, .394], respectively). The same applied to supervisor support (Estimate = .092, 95% CI [.024, .208], and Estimate = .157, 95% CI [.035, .333], respectively). However, in the relationships between co-worker, supervisor support and exhaustion, only psychological flexibility played a mediating role. In conclusion, social support in nursing is a job resource that is associated with high levels of energy and motivation among nurses through the mediating role of certain job demands and personal resources.